Materials science and technology: past, present and the future - Kassim, Anuar (2005)
There are many questions ask, but not all can be answered (precisely) about matter, its diversity, our existence in this universe and also our relationship with technology. Research shows that matter comes from big explosion, called The Big Bang that produced building blocks particles, and later formed lightest atom. At the centers of bug galaxies, heavy atoms were formed and distributed in the universe through explosions of stars and collisions of galaxies. All these atoms, when combined to form molecules or compounds, are called materials. The existence of “Man” through the eyes of science, were made from materials in the universe through evolution process. Since, survival is the keyword for human existence, man needs material to interact with its surrounding, and this is called technology. Many civilizations use different type of materials and technology but the most significance civilization is in the era of the twentieth century, called the golden era of the century, where the amount of scientifically gained knowledge is at an exponential rate. Many new materials were found and applied to the relevant technology. To survive further in the future, man not only walk on the planet, he needs to go up, “outerspace”, to seek new frontier of knowledge and materials that is impossible to acquire on earth. New and future materials to be produced need new environment (sophisticated laboratory, laboratory in outerspace or deep in the ocean floor or on other planets) and that will demand superior technology. The needs to be in outerspace, materials that can overcome the harsh and violent environment were needed. All these need scientifically technique/method called research, which will keep man busy playing with the gift from god, matter. Several current researchers done on materials science are also highlighted. The objectives of this presentation are to highlight the source of matter or the materials in the universe, man interaction with materials in its surrounding, the technology, and also looking for the type of materials and technology that is possible for human being to survive in the future.